Iron content in fruits, vegetables, herbs and spices samples marketed in Sarajevo, Bosnia and Herzegovina - Bukva, Mersa; Kapo, Delila; Huseinbašić, Nudžeima; Gojak-Salimović, Sabina; Huremović, Jasna (2019)
Iron deficiency anaemia is one of the major health problems that affects cognitive performance, physical capacity, immune status, and reproductive performance. The iron content in 35 food samples (fruits, vegetables, herbs, and spices) marketed in Sarajevo, Bosnia and Herzegovina was determined. Тhe iron content in the fruits and vegetables was determined using FAAS spectrometry, and in the herbs and spices samples by UV/Vis spectrophotometry. Experimentally determined content was: fruits (2.91–39.27 mg kg–1), vegetables (6.33–107 mg kg–1), herbs (135–962 mg kg–1), and spices (59.00–918 mg kg–1). Daily intakes for different plant samples were also calculated. The food samples were arranged by iron concentration in the following descending order: herbs and tea >spices >vegetables >fruits. The results from this study were compared with previously published data. The obtained values are in the area of common values. The iron content and the factors that increase its bioavailability can help in the selection of proper foods to be included in the daily diet.
Anemija zbog nedostatka željeza, jedan je od glavnih zdravstvenih problema, a utječe na kognitivne sposobnosti, fizički kapacitet, imunološki status i reproduktivnu sposobnost. Utvrđen je sadržaj željeza u ukupno 35 uzoraka hrane (voće, povrće, ljekovito bilje i začini) s tržišta u Sarajevu u Bosni i Hercegovini. Sadržaj željeza u voću i povrću određen je FAAS spektrometrijom, a u uzorcima ljekovitog bilja i začina UV/Vis spektrofotometrijom. Utvrđen je sljedeći sadržaj: voće (2,91 – 39,27 mg kg–1), povrće (6,33 – 107 mg kg–1), ljekovito bilje (135 – 962 mg kg–1) i začini (59,00 – 918 mg kg–1). Također su izračunati dnevni unosi za različite uzorke biljnog materijala. Prema koncentracijama željeza uzorci su raspoređeni u sljedećim serijama: ljekovito bilje >začini >povrće >voće. Rezultati ovog istraživanja uspoređeni su s prethodno objavljenim podatcima. Dobivene vrijednosti nalaze se u području literaturnih podataka. Sadržaj željeza i čimbenici koji povećavaju njegovu bioraspoloživost mogu pomoći u odabiru odgovarajuće hrane za svakodnevnu prehranu.
Bibliografija: 42 jed.
Summary ; Sažetak.
Keywords: Voće -- Povrće -- Željezo -- Začini -- Ljekovito bilje -- Spektrofotometrija